Drug resistance, serotypes, and phylogenetic groups among uropathogenic Escherichia coli including O25-ST131 in Mexico City - Molina-López, José; Aparicio-Ozores, Gerardo; Ribas-Aparicio, Rosa María; Gavilanes-Parra, Sandra; Chávez-Berrocal, María Elena; Hernández-Castro, Rigoberto; Manjarrez-Hernández, Hipólito Ángel (The Journal of Infection in Developing Countries, 2011)
Introduction: The increasing prevalence of uropathogenic Escherichia coli (UPEC) strains resistant to multiple antibiotics complicates the treatment of urinary tract infections (UTIs). This study aimed to analyze the antimicrobial resistance, serotypes, and phylogenetic groups among strains of E. coli isolated from outpatients with UTIs in Mexico City. Methodology: A total of 119 E. coli isolates were recovered from urine samples from outpatients with clinical diagnosis of uncomplicated UTIs from 2004 to 2007. The serotype was assessed by agglutination in microtiter plates; susceptibility to antimicrobials was determined by the disk diffusion method. Clone O25-ST131 and phylogenetic groups of E. coli strains were tested by methods based on PCR multiplex. Results: The predominant serotype was O25:H4 (21.2%). Resistance to antibiotics was ampicillin (83.7%); piperacillin (53.8%); the fluoroquinolone group (55.5-60.6%), and trimethoprim/sulfamethoxazole (TMP/SMX) (56.4%). Additionally, 36 (30.2%) isolates were multidrug-resistant and 13 of these 36 strains were identified as E. coli O25-ST131 clone by an allele-specific PCR-based assay. Phylogenetic analysis showed that 15 of 17 isolates with serotype O25:H4 belonged to group B2. Conclusions: This is the first report that establishes the presence in Mexico of the O25-ST131 clonal group of E. coli, which has been associated with multidrug-resistance and with high virulence potential. The spread of this clone in Mexico should be monitored closely. We found a correlation between serotype O25:H4 and multidrug resistance in UPEC strains. Our results indicate that the use of ampicillin, fluoroquinolones, and TMP/SMX should be reviewed when selecting empirical therapy for UTIs.